Prototipo de un aplicativo para el analisis del crecimiento y desarrollo oseo-dental en pacientes de odontologia, colombia (2020)
Currently, it is clear that both in the children's clinics of the Universidad Antonio Nariño Sede Ibagué and among the specialists in orthodontics and maxillary orthopedics of Colombia, there is no technological application available that provides the ability to perform, unify and expedite the analyzes of growth and development of the bone-dental. When carrying out the inter-consultations with other specialists in the orthodontic, maxillary orthopedic and pediatric branches, there are deficiencies in the passing of information from the studies carried out to the patient since each specialist has a personal opinion or criterion regarding the diagnosis and treatment plan. There is no alternative diagnosis or a different opinion that can complement a little more the decisions made regarding the patient's treatment plan. On the other hand, it was found that there are about 246 technological applications available in the area of dentistry and 239 for orthodontics. They are mostly digital games or support for the management of clinics, as well as teaching oral hygiene habits.